On-farm banana (Musa) cultivar diversity status across different altitudes in North and South Kivu provinces of eastern Democratic Republic of Congo - Ocimati, W.; Karamura, D.; Sivirihauma, Charles; Ndungo, V.; Langhe, E. de; Adheka, J.; Dheda Djailo, B.; Ntamwira, J.; Muhindo, H.; Ragama, P.E.; Blomme, Guy (International Society for Horticultural Science, 2016)
A Musa germplasm diagnostic study assessed on-farm Musa diversity and farmer selection criteria in different altitudes of North Kivu (NK) and South Kivu (SK) in eastern Democratic Republic of Congo, an important zone of secondary diversification of plantains (AAB genome) and East African highland bananas (EAHB, AAA genome). Diversity was defined using the indices of richness and dominance/evenness. More cultivars (35) were recorded in SK compared to NK (32). However, NK sites had higher cultivar evenness compared with SK. For example, 21 cultivars were grown widely (in three localities) in NK compared with 12 in SK. Long-term on-farm Musa diversity conservation will hence be easier in NK. Cooking EAHB cultivars (35% of Musa landscape) dominated in NK, followed by beer (27%, EAHB + ABB), plantain (21%) and dessert (AAB + AAA, 17%) cultivars. Cooking cultivars were grown across all altitudes, while beer types dominated at the higher altitudes of Munoli (1,733 m) and plantains at the low altitudes in Mutwanga (1,049 m) and Mangodomu (969 m). SK, with predominantly high altitudes (1,553 to 1,992 m), was dominated by beer types (72%). 'Vulambya' (EAHB cooking, 22%), 'Nguma' (plantain, 13%), 'Tundu' (EAHB beer, 10%), 'Pisang Awak' (ABB genome, Pisang Awak subgroup, beer, 8%), and 'Mukingiro' (EAHB beer, 7%) dominated in NK, while 'Nshikazi' (EAHB beer, 66%) dominates in SK. Tolerance of infertile soil, pest and disease resistance and availability of planting materials were key farmer selection criteria that influenced Musa diversity on-farm. Ex situ conservation of rare cultivars with limited cultural importance is recommended to prevent genetic erosion.